Climatic zoning of Xinjiang for heterogeneous production of high-quality wine - Xue Feng; Tang Xiang-ling (Scientific Reports)
Abstract To diversify wine production in Xinjiang and address the issue of wine homogenization, it is crucial to leverage the unique climatic advantages of each grape-producing area to foster a high-quality wine industry. Using meteorological data from 80 national standard meteorological stations in Xinjiang, spanning 1961 to 2019, this study established a climatic zoning index system tailored to distinct grape varieties for wines, including dry red, dry white, ice wine, sparkling wine, and natural sweet wines. The system is formulated based on key climatic factors such as the frost-free period, ≥ 10 °C active accumulated temperature (AAT10), mean temperature of the coldest month, annual extreme minimum temperature, and dryness. The fine climatic zoning for wine grapes in Xinjiang was created using GIS spatial interpolation technology. The findings reveal that Xinjiang’s four traditional wine grape growing areas are ideally suited for cultivating high-quality dry red and dry white wine grapes. The premium planting areas for natural sweet wine grapes are concentrated primarily in the northern Tarim Basin in southern Xinjiang and the southern Junggar Basin at the northern foothills of the Tianshan Mountains. The sparkling wine grape cultivation area is scarce in Xinjiang, with only a small, high-quality segment located in the Emin region of the Tacheng Basin. As for ice wine grapes, Xinjiang has limited growing areas, with scattered cultivable patches found in the Yili River Valley and the Tacheng Basin. Notably, the Tacheng Basin, a non-traditional wine grape region, contains high-quality grape growing area for dry white and sparkling wines, including the only high-quality area for sparkling wine. This diversification potential could enhance Xinjiang’s capacity to develop and expand its premium dry white wines and expand its range of wine offerings.